2019
DOI: 10.1111/apt.15227
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal 5‐aminosalicylic acid concentration, drug formulation and mucosal microbiome in patients with quiescent ulcerative colitis

Abstract: Summary Background 5‐aminosalicylic acid (5‐ASA) is the first‐line therapy for ulcerative colitis (UC). 5‐ASA acts locally in the colonic mucosa by numerous proposed mechanisms, and is metabolised by N‐acetyltransferase (NAT). Large variations in mucosal 5‐ASA concentrations have been reported, but the underlying mechanisms are not understood. Aim To study the relationship between 5‐ASA concentration, 5‐ASA formulation, NAT genotype and bacterial microbiome in patients with UC. Methods Patients with quiescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 50 publications
(73 reference statements)
2
40
0
Order By: Relevance
“…Xu et al [ 4 ] demonstrated a higher abundance of Firmicutes and lower levels of Proteobacteria in the inflamed mucosa of 5-ASA-treated patients. Olaisen et al [ 5 ] determined that the mucosal 5-ASA concentration was positively associated with mucosal bacterial diversity and bacterial compositions. A high mucosal 5-ASA concentration was also found to be related to the reduced abundance of pathogenic bacteria such as Proteobacteria and increased abundance of several favorable families (Lachnospiraceae and Ruminococcaceae) and genera such as Faecalibacterium and Coprococcus .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu et al [ 4 ] demonstrated a higher abundance of Firmicutes and lower levels of Proteobacteria in the inflamed mucosa of 5-ASA-treated patients. Olaisen et al [ 5 ] determined that the mucosal 5-ASA concentration was positively associated with mucosal bacterial diversity and bacterial compositions. A high mucosal 5-ASA concentration was also found to be related to the reduced abundance of pathogenic bacteria such as Proteobacteria and increased abundance of several favorable families (Lachnospiraceae and Ruminococcaceae) and genera such as Faecalibacterium and Coprococcus .…”
Section: Introductionmentioning
confidence: 99%
“…5-ASA may have beneficial effects on the mucosal microbiome, with high concentrations altering dysbiosis in UC. Olaisen et al [ 5 ] highlighted that mucosal 5-ASA concentration is associated with changes in mucosal bacterial composition, however, the fecal microbiota was not changed to the same extent.…”
Section: Introductionmentioning
confidence: 99%
“…The authors' declarations of personal and financial interests are unchanged from those in the original article …”
Section: Acknowledgementsmentioning
confidence: 99%
“…We welcome the interest expressed by Buchner and Lichtenstein in our work examining mucosal mesalazine concentration in relation to various factors, including the microbiome composition in mucosal biopsies and faecal samples from patients with ulcerative colitis (UC) …”
mentioning
confidence: 99%
“…The recent study by Dr. Olaisen et al in AP&T adds a valid argument for the influence of 5‐ASA on the mucosal microbiome. The study aimed to evaluate the relationship between 5‐ASA concentrations, 5‐ASA formulations, N‐acyl transferase (NAT) genotype and bacterial microbiome in 42 patients with UC.…”
mentioning
confidence: 92%